ATTRIBUTION OF TEAM MEMBERS' RESPONSIBILITY: THE EFFECT OF TEMPORAL PATTERN OF PERFORMANCE - Kaiser, Donn L.; Barnett, Mark A. (Social behavior and personality, 1978)
Two experiments were conducted to assess the effects of an individual's temporal pattern of success on attributions of responsibility for winning or losing a simulated free throw contest. In Experiment 1, subjects observed, via videotape, two teammates shooting free throws against an opposing team who had already completed their shots. The outcome (win or lose) of the contest was manipulated as well as the time at which one player made his shots (beginning or end of game). In Experiment 2, individual and team performance information was given to subjects without the videotape. In both experiments the player on a winning team who scored at the end was judged as more responsible for the outcome than when he succeeded at the beginning. When the team lost, however, succeeding at the beginning or end did not have an effect on responsibility attributions.